1999
DOI: 10.1021/jp9837885
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Stretching Vibrational Circular Dichroism in Methyl Lactate and Related Molecules

Abstract: The CH- and OH-stretching vibrational circular dichroism (VCD) spectra of methyl lactate and related molecules in CCl4 solution have been investigated to identify solution conformations and establish a correlation between OH- and methine-stretching VCD intensity and molecular structure. Deuterium substitution was used when possible to remove overlapping absorption features in the CH-stretching region. Anisotropy ratios between +2.1 × 10-4 and +2.8 × 10-4 were measured for the methine-stretching VCD of the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
69
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(75 citation statements)
references
References 43 publications
6
69
0
Order By: Relevance
“…In particular, these absorptions are due to the stretching vibration of OH groups that are hydrogen bonded to either C O or O-CH 3 groups attached to the vicinal chiral carbon [12,13].…”
Section: Oh Stretching Bandmentioning
confidence: 99%
“…In particular, these absorptions are due to the stretching vibration of OH groups that are hydrogen bonded to either C O or O-CH 3 groups attached to the vicinal chiral carbon [12,13].…”
Section: Oh Stretching Bandmentioning
confidence: 99%
“…However, with a single exception, previous experimental studies on this molecule were only able to detect the expectedly most stable SsC conformer [21][22][23]. Experimental evidence of the higher energy forms of MLac was only reported hitherto by Freedman, Nafie and coworkers [24,25], who have studied this compound in CCl 4 solution by vibrational circular dichroism (VCD). These authors examined the C-H and OH stretching spectral regions of the VCD spectrum of MLac and, by comparison with the corresponding calculated spectra obtained at the DFT(B3LYP)/6-31G(d) level of theory, were able to identify in the studied regions spectral features that can be ascribable to the major SsC form and to the two minor conformers having the OH Á Á Á O ester intramolecular H-bond (GskC and G 0 sk 0 C) [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Experimental evidence of the higher energy forms of MLac was only reported hitherto by Freedman, Nafie and coworkers [24,25], who have studied this compound in CCl 4 solution by vibrational circular dichroism (VCD). These authors examined the C-H and OH stretching spectral regions of the VCD spectrum of MLac and, by comparison with the corresponding calculated spectra obtained at the DFT(B3LYP)/6-31G(d) level of theory, were able to identify in the studied regions spectral features that can be ascribable to the major SsC form and to the two minor conformers having the OH Á Á Á O ester intramolecular H-bond (GskC and G 0 sk 0 C) [24,25]. To the best of our knowledge no other studies on the conformational preferences and vibrational properties of monomeric MLac have been reported hitherto.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…26,27 Excellent agreement between experimental and calculated VCD spectra 27,28 has confirmed the reliability of calculations on metal complexes of moderate size and hydrogen stretching motions, which have been carried out at the DFT level with gauge invariant atomic orbital (GIAO). [28][29][30][31] Meantime, some DFT and ab initio studies concentrated on the molecular properties of cisplatin and its analogues were reported.…”
Section: Introductionmentioning
confidence: 99%